2019
DOI: 10.1002/eco.2126
|View full text |Cite
|
Sign up to set email alerts
|

Effects of land‐cover changes on the partitioning of surface energy and water fluxes in Amazonia using high‐resolution satellite imagery

Abstract: Spatial variability of surface energy and water fluxes at local scales is strongly controlled by soil and micrometeorological conditions. Thus, the accurate estimation of these fluxes from space at high spatial resolution has the potential to improve prediction of the impact of land-use changes on the local environment. In this study, Advanced Spaceborne Thermal Emission and Reflection Radiometer (ASTER) and Large-Scale Biosphere-Atmosphere Experiment in Amazonia (LBA) data were used to examine the partitionin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 100 publications
(169 reference statements)
3
26
0
Order By: Relevance
“…Our estimates of energy partition (sensible and latent heat) for different land uses are in accordance with Restrepo-Coupe et al [117], who showed that converted areas (forest to cropland and pasture) presented a different behavior with relative reductions in dry season ET, consistent with increasing water limitation due to loss of deep roots that can access soil water. They are also in agreement with Oliveira et al [118] and Dias et al [4], who conducted studies in the southwest (Ji-Paraná River basin) and southeast (Xingu River basin) Amazon on the conversion between forest vegetation and cropland and pasture, showing substantial changes on surface energy (H and LE) and water (ET) fluxes. Furthermore, changes in β reflect alterations on surface energy fluxes partitioning between H and LE.…”
Section: Spatial Assessment Of Surface Energy and Water Fluxessupporting
confidence: 91%
“…Our estimates of energy partition (sensible and latent heat) for different land uses are in accordance with Restrepo-Coupe et al [117], who showed that converted areas (forest to cropland and pasture) presented a different behavior with relative reductions in dry season ET, consistent with increasing water limitation due to loss of deep roots that can access soil water. They are also in agreement with Oliveira et al [118] and Dias et al [4], who conducted studies in the southwest (Ji-Paraná River basin) and southeast (Xingu River basin) Amazon on the conversion between forest vegetation and cropland and pasture, showing substantial changes on surface energy (H and LE) and water (ET) fluxes. Furthermore, changes in β reflect alterations on surface energy fluxes partitioning between H and LE.…”
Section: Spatial Assessment Of Surface Energy and Water Fluxessupporting
confidence: 91%
“…Amazonian droughts are triggered by ocean conditions: El Niño Southern Oscillation (ENSO) events were important in the droughts of 1982, 1987, 1997–1998, and 2015, while droughts in 2005 and 2010 were mainly caused by high sea surface temperature anomalies in the North Atlantic Ocean, which created a dipole that increased subsidence and decreased rainfall over the southern Amazon (Marengo et al., 2015; Zeng et al., 2008). Land surface conditions can either mitigate or exacerbate reduced moisture supply from the ocean: Forest and pasture systems both have deep roots that allow them to access moisture and maintain ET even during drought conditions (Hodnett et al., 1996b; Nepstad et al., 1994), thereby maintaining water supply to the atmosphere, though pastures are generally more sensitive to drought than forests (Oliviera et al., 2019), and a reduction in ET by pastures could exacerbate drought. While ocean conditions are important drivers of drought, the role of forest and nonforest cover in mitigating or exacerbating drought in agricultural areas of the Amazon have not been quantified.…”
Section: Introductionmentioning
confidence: 99%
“…Investigations of the impact of forest structure gradients and change on albedo typically contrast forest with highly altered vegetation types canopies. For example, higher albedo is typically found in pasture, crops, and cleared lands, relative to forest, at least after initial post‐fire increases in absorptive charred materials subside (de Oliveira and Moraes 2013, de Oliveira et al 2016, 2019, Faria et al 2018). The albedo of regenerating secondary forest appears to converge toward mature forest values (low values, i.e., ~0.1); however, seasonal differences in albedo and net radiation appear linked to structure in these forests (de Oliveira and Moraes 2013, de Oliveira et al 2016, 2019).…”
Section: Section 1: Reframing Tropical Forest Savannization As Transimentioning
confidence: 99%
“…For example, higher albedo is typically found in pasture, crops, and cleared lands, relative to forest, at least after initial post‐fire increases in absorptive charred materials subside (de Oliveira and Moraes 2013, de Oliveira et al 2016, 2019, Faria et al 2018). The albedo of regenerating secondary forest appears to converge toward mature forest values (low values, i.e., ~0.1); however, seasonal differences in albedo and net radiation appear linked to structure in these forests (de Oliveira and Moraes 2013, de Oliveira et al 2016, 2019). Foundational energy and materials flux network studies highlight large scale gradients in Amazon forest function, including variation in seasonal patterns and the roles of water vs. radiation limitation of photosynthesis and latent and sensible heat fluxes (da Rocha et al 2009, Restrepo‐Coupe et al 2013).…”
Section: Section 1: Reframing Tropical Forest Savannization As Transimentioning
confidence: 99%
See 1 more Smart Citation